Association of rivaroxaban plasma trough concentrations with clinical characteristics and outcomes - Wu, Huizhen; Yu, Qiaoling; Jin, Panpan; Huo, Lijing; An, Jing (Frontiers in Pharmacology, 2025)
BackgroundRivaroxaban use has increased significantly among older adults; however, no definitive plasma concentration thresholds for bleeding or thrombosis have been established. However, dose adjustments for this population remain controversial.MethodsBetween January 2022 and August 2023, we analyzed trough plasma samples from hospitalized patients treated with rivaroxaban for at least three consecutive days. Clinical data, including demographics, comorbidities, and adverse events, were extracted from electronic medical records. The plasma concentrations of rivaroxaban were measured using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Statistical analyses were performed to identify factors influencing rivaroxaban exposure and clinical outcomes.ResultsAmong 360 plasma samples analyzed (55% male; median age: 72 years), age (P = 0.042) and renal function (P = 0.002) were significant predictors of rivaroxaban concentration-to-dose ratio. Bleeding events were associated with higher trough concentrations (median: 81.85 ng/mL in the bleeding group vs. 26.80 ng/mL in others; P < 0.001) and were more common in patients with malignancies or prior bleeding history. Thrombotic events occurred predominantly in older patients with a history of stroke (P < 0.05). Patients who died were older and had higher CHA2DS2-VASc scores (P < 0.05), prolonged prothrombin times (P < 0.001), and multiple comorbidities.ConclusionRoutine monitoring of rivaroxaban plasma concentrations may improve safety in older adults with multiple comorbidities or impaired hepatic, renal, or coagulation functions. Further research is required to establish specific therapeutic thresholds for bleeding and thrombosis.